Améliorer l’accès des personnes âgées de Saint-Boniface et de Saint-Vital aux services de santé en français. Objectif 5 - Description des expériences de trajectoires individuelles de soins de santé en français pour les aînés | Improving St. Boniface and St. Vital seniors' access to French-language health services. Objective 5 - Description of experiences of seniors' individual trajectories in French-language health care - Éthier, Sophie; Ba, Halimatou; Belzile, Louise; Gagné, Maryanne; Roch-Gagné, Margaux (Conseil communauté en santé du Manitoba et Université de Saint-Boniface, 2012)

L'influence du contexte sociolinguistique minoritaire sur le maintien à domicile des aînés en milieu rural dévitalisé : le cas d’Acadieville au Nouveau-Brunswick - Simard, Majella; Dupuis-Blanchard, Suzanne; Villalon, Lita; Gould, Odette; Ethier, Sophie; Gibbons, Caroline (La Revue canadienne du vieillissement, 2015)
New Brunswick is one of the provinces most affected by the aging of the population. Moreover, aging at home in Francophone minority communities is a major challenge in rural areas. The goal of this paper is to identify the main advantages and disadvantages of aging at home and to expose organizational strategies deployed by seniors and their families in order to promote aging in place. The case study is the method of analysis that we have recommended. Our methodology is based on content analysis of 13 semi-structured interviews with seniors and their children. The results show that family and community support, resourcefulness and resiliency, the practice of leisure activities as well as the living environment are among the principal means used by older adults to promote aging at home.

Strategies for aging in place: The experience of language-minority seniors with loss of independence - Dupuis-Blanchard, Suzanne; Gould, Odette N.; Gibbons, Caroline; Simard, Majella; Éthier, Sophie; Villalon, Lita (Global Qualitative Nursing Research, 2015)
For healthy and independent older adults, aging in place can be seen as identical to any other adult living at home. Little is known about how frail seniors, particularly those who speak a minority language, manage the challenges of aging in place. The present qualitative descriptive study explores the strategies that Canadian French-speaking seniors have put in place to counter their loss of independence and promote their ability to stay in their home. Semistructured individual interviews were conducted with 39 older adults and transcribed, followed by content analysis to identify common themes related to study objectives. Six themes emerged in response to strategies described for aging in place. Findings reveal the limited extent to which language issues were perceived as a barrier by participants. In conclusion, the results of this study provide us with fruitful insights to guide community nursing practice, future research, and public policy.